Hands-on Experience of THERMO FITNESS TESTING Device Use for Thermoelectric Evaluation of Metallic Materials - A. A. Soldatov; A. I. Soldatov; M. A. Kostina; A. A. Abouellail (Приборы и методы измерений, 2024)
The article describes experience of practical application of the differential thermoelectric tester "THERMO FITNESS TESTING". Description of the sensor design and results of differential thermoelectromotive force measurement for a large group of metals widely used in Russia are given. Usage of the "THERMO FITNESS TESTING" device to test the quality of R6M5 steel heat treatment is described. Dependence of thermoelectromotive force on the heating temperature which can be used for practical purposes was obtained. Usage the "THERMO FITNESS TESTING" to measure the thickness of a cemented (carburized) layer of 12KH2N4А steel is considered. Dependence of the thermoelectromotive force on the thickness of the cementation layer was also obtained.